Analysis And Redesigning Of Key Result Areas (kras) For A Private Company With Special Reference To Extinct Fire Engineers Private Limited At Mumbai - Jain, Arjita (Gyan Management Journal, 2020)
Key Result Areas (KRAs) refer to general areas of outcomes for which a role, or a combination of roles, is responsible. These are the areas within the organization where an individual/group, is responsible for the results. As Extinct Fire was undergoing the organizational restructuring process, there was a strong need for redesigning Job Descriptions and the KRAs. Researcher was engaged in redesigning the KRAs various levels at length. The data was collected internally from variousdepartments by scanning old KRA documents; which were discussed with department wise individual team membersand approved by respective Head of the Department and sanctioned by Managing Director. The Standard Operating Procedureswere made after the collection of the information by meeting and discussion held with departmental head. New KRAs were finalized; entire redesigning process was carried out under the guidance of head HR. The Redesigning of KRAs was carried out in 13 Departments: Enterprise Resource Planning (ERP) Department, Maintenance Contract (AMC) Department, Information and Technology Department, Design Department, Purchase Department, Planning & MIS Department, Human Resource Department, Marketing Department, Accounts & Finance Department, Projects Department, Estimation Department, Contracts Department, and for total 263 (Departments + Site Staff) positions KRA Redesigning was carried out. This paper presents the working of few selected departments.